Analisis Pembubaran Ormas Tanpa Proses Peradilan Pasca Penetapan UU No. 16 Tahun 2017 Tentang Ormas - Nur Aji Pratama (Rechtenstudent, 2020)
The background of the amendment to the Law on Community Organization was due to the inadequacy of regulations regarding the problems that existed at that time. Changes in the regulation of the dissolution of community organizations without due process of law which are replaced by the principle of contrario actus constitute a matter that needs to be reviewed on a constitutional basis in a state that declares a state of law (rechtstaat) and not a power state (machtstaat). The focus of the problems examined in this thesis are: 1) What is the background of the emergence of Law Number 16 of 2017 concerning Community Organizations? 2) What is the constitutionality of the authority to dissolve community organizations without a judicial process? The objectives of this study are: 1) Describe the background of the emergence of the Law on Community Organization and the critical analysis of researchers towards this Law. 2) Describe the analysis of the constitutionality of the authority to dissolve community organizations without a judicial process. To identify these problems, this study uses normative legal research which is a qualitative analysis using a statute approach, a conceptual approach, and a case approach. This research draws the following conclusions: 1) The old regulation is no longer adequate, so it demands an amendment to the Law. 2) The policy to dissolve the organization without a judicial process is an unconstitutional policy.